Clinical Decision-Making in Palliative Care Nursing in Kazakhstan: A Qualitative Study - Aimbetova , Gulshara; Issenova , Balday; Lyazat, Orakbay; Tursynbekova, Anar; Anartayeva , Mariya; Akhmetov, Valikhan; Maxudova , Makhigul; Bukhaeva, Zhanerke; Serikova , Saltanat; Zhakupova, Maiya (Bangladesh Journal of Medical Science, 2025)
Background Clinical decision-making in palliative care is crucial for providing quality care to individuals with life-limiting illnesses. Nurses, as key members of the palliative care team, make critical decisions regarding symptom management, patient comfort, and end-of-life care. In Kazakhstan, where palliative care is still evolving, understanding how nurses make these decisions is essential to improving care quality and informing healthcare policies. Aim This study aimed to explore the clinical decision-making experiences of palliative care nurses in Kazakhstan, focusing on the factors influencing their decisions, the challenges they encounter, the strategies they employ, and how decision-making processes can be improved. Methods A qualitative research design was employed, using semi-structured interviews with 12 palliative care nurses from various healthcare settings across Kazakhstan. Participants were selected through purposive sampling to ensure a diverse representation of experiences from both urban and rural areas. The interviews were transcribed verbatim and analyzed using thematic analysis to identify key patterns and themes related to clinical decision-making. Results The analysis revealed several factors influencing decision-making, including clinical knowledge and experience, patient and family preferences, and systemic factors such as resource constraints. Nurses reported challenges such as cultural reluctance to discuss death, lack of formal palliative care training, and limited access to medications and equipment, particularly in rural areas. To address these challenges, nurses employed strategies like interdisciplinary collaboration, patientcentered care, and a strong desire for ongoing education. Conclusion Clinical decision-making in palliative care nursing in Kazakhstan is shaped by a combination of clinical expertise, cultural dynamics, and systemic limitations. The findings highlight the need for formal education, improved resource availability, and better interdisciplinary collaboration to support nurses in making informed and effective decisions. Enhancing these aspects can significantly improve the quality of palliative care in Kazakhstan, ensuring that decisions align with the values and wishes of patients and their families. BJMS, Vol. 24 No. 03 July’25 Page : 967-974